Research into interdependence of economic activities in the context of the rural sector of economy of the region - T. D. Degtyaryova; E. A. Chulkova (Экономика региона, 2010)
The paper considers interactive influence of certain types of economic activity within the rural sector on the region's agricultural production. The major interdependence has been established, the correlation-regression analysis has been conducted. The dependence is represented by the linear equations of multiple regression. High percentage of variation of the resultant indicator (gross agricultural output in all categories of the industry) is explained by the models built. Over the entire period the production of livestock and poultry has had maximal influence on the given indicator. The gross yield of grain is the second significant factor.